Fra-1 Inhibits Cell Growth and the Warburg Effect in Cervical Cancer Cells via STAT1 Regulation of the p53 Signaling Pathway - Zhang, Manying; Liang, Lin; He, Junyu; He, Zhengxi; Yue, Chunxue; Jin, Xi; Gao, Mengxiang; Xiao, Songshu; Zhou, Yanhong (Frontiers in Cell and Developmental Biology, 2020)
The oncogenesis of cervical cancer is a multi-factor and multi-step process, and major risk factors include oncogene activation with tumor suppressor gene inactivation, viral factors, and immune factors. For example, the human papillomavirus has been linked to the occurrence of cervical cancer. At present, the pathogenesis of cervical cancer remains unclear. Fra-1 is a member of the Fos family and an important nuclear transcription factor that regulates normal cell growth, differentiation, and apoptosis. In the present study, we found that Fra-1 inhibited the proliferation of cervical cancer cells while also promoting apoptosis and affecting cell cycle distribution. Moreover, Fra-1 up-regulated STAT1 expression and modulated p53 signal pathway activity in cervical cancer cells. Overexpression of Fra-1 inhibited cell senescence by altering sirtuin 1 (SIRT1) expression in HeLa cells, and Fra-1 overexpression restored mitochondrial disorder and suppressed metabolic reprogramming in HeLa cells. Silencing of STAT1 impaired the inhibitory effect of Fra-1 on cervical cancer cell growth, while knock-down of STAT1 reversed the effect on cell senescence and mitochondrial dysfunction caused by Fra-1 in HeLa cells. Silencing of STAT1 also recovered metabolic reprogramming in cervical cancer cells. In summary, our results show that Fra-1 inhibited cervical cancer cell growth and the Warburg effect via STAT1-mediated regulation of the p53 signaling pathway.